Perform kicking with or without jumping: joint coordination and kinetic differences between Taekwondo back kicks and jumping back kicks - Cheng, K. B.; Wang, Y.-H.; Kuo, S.-Y.; Wang, K.-M.; Huang, Y.-C. (Journal of Sports Sciences, 2015)
We investigated joint coordination differences between Taekwondo back kicks and jumping back kicks, and how jumping (in performing the latter) would alter engaging ground reaction forces (GRF) in executing kicking. Ten skilful athletes volunteered to perform both kinds of kicking within the shortest time for three successful trials. Three high-speed cameras and two force platforms were used for data collection, and the trial with the shortest execution time was selected for analysis. Movements were divided into the rotation and attack phases. With comparable execution time and maximum joint linear/angular speeds, back kicks and jumping back kicks differ mainly in larger GRF in the latter, and in greater target acceleration in the former probably because the support leg prevented athletes` rebounding after impact. In addition, more prominent antiphase and in-phase coordination between the shoulder segment and knee joint, and elongated rotation phase were found in jumping back kicks. Larger GRF values in jumping back kicks were generated for jump take-off rather than for a more powerful attack. In back kicks although the support leg remained ground contact, greatly decreased GRF in the attack phase suggested that the support leg mainly served as a rotation axis.